OVARIAL RESERVE IN WOMEN OF THE KUZBASS AT THE ART PLANNING STAGE - Trishkin , Aleksey Gennadievich; Shadrintsev, Vladimir Alexandrovich; Plavko, Marina Nikolaevna; Еlgina, Svetlana Ivanovna; Rudaeva, Elena Vladimirovna; Moses, Vadim Gelievich; Shmelev, Alexey Andreevich; Bochkarnikova, Asmik Gerbertovna; Moses, Kira Borisovna (Mother and Baby in Kuzbass, 2026)
Ovarian reserve is the number of eggs in a woman's ovaries. It is estimated based on the number of antral follicles (CAF) according to ultrasound data, as well as the levels of AMH and FSH in the blood. With each menstrual cycle, this reserve decreases irreversibly, and after the age of 35, the decrease accelerates. Age is an important factor that affects the effectiveness of infertility treatment, including assisted reproductive technologies. An analysis of indicators by age group showed that women under the age of 34 have a more favorable pregnancy rate, while women aged 35 and older have a significantly lower chance of successful conception.
Keywords: infertility; ovarian reserve; ART